2012
DOI: 10.1111/j.1476-5381.2012.01987.x
|View full text |Cite
|
Sign up to set email alerts
|

Positive allosteric modulation by ivermectin of human but not murine P2X7 receptors

Abstract: BACKGROUND AND PURPOSEIn mammalian cells, the anti-parasitic drug ivermectin is known as a positive allosteric modulator of the ATP-activated ion channel P2X4 and is used to discriminate between P2X4-and P2X7-mediated cellular responses. In this paper we provide evidence that the reported isoform selectivity of ivermectin is a species-specific phenomenon. EXPERIMENTAL APPROACHComplementary electrophysiological and fluorometric methods were applied to evaluate the effect of ivermectin on recombinantly expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 56 publications
3
79
0
Order By: Relevance
“…Because high concentrations of these compounds may also modulate other receptor systems or ion channels like it is known for IVM [20], their selectivity must be verified in more detail. The potential for further structural modifications make the three natural products investigated attractive starting points for further optimization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because high concentrations of these compounds may also modulate other receptor systems or ion channels like it is known for IVM [20], their selectivity must be verified in more detail. The potential for further structural modifications make the three natural products investigated attractive starting points for further optimization.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3a illustrates the modulatory effects of the three investigated natural compounds as well as those of some reference substances: the competitive tetrazole P2X7 antagonist A-438079 [18], the highly potent non-competitive P2X7 antagonist AZ 10606120 [19] and the antiparasitic drug IVM, recently described as a positive allosteric modulator of human P2X7 in the same cell line [20]. (Fig.…”
Section: Analysis Of Concentration Dependence By [Ca 2+ ] I Measurementsmentioning
confidence: 99%
“…Isolation of Human Macrophages-Monocyte-derived macrophages were obtained as described by Norenberg et al (58). Blood obtained from healthy volunteers was centrifuged at 500 ϫ g for 10 min to isolate plasma, buffy coat layer, and erythrocytes.…”
Section: Methodsmentioning
confidence: 99%
“…Ivermectin (IVM), an antiparasitic drug used in humans and animals, is a selective positive modulator of P2X4Rs [20,21]. We have shown that IVM antagonizes ethanolmediated inhibition of P2X4Rs in vitro [12].…”
Section: Introductionmentioning
confidence: 99%